2012
DOI: 10.4414/smw.2012.13742
|View full text |Cite
|
Sign up to set email alerts
|

Lobar lung resection in elderly patients with non-small cell lung carcinoma: impact of cardiac comorbidity on surgical outcome

Abstract: In our experience lobar lung resections for NSCLC in elderly patients with cardiac comorbidity seem to be a safe therapy option for this increasing subpopulation. Though, our retrospective data with the small number of study objects require further confirmation in larger prospective trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Although the possibility for in-hospital death was estimated to be three times higher for the right-sided pneumonectomy compared to lobectomy or limited lung resection, the risk of death following pneumonectomy or extended resection was not correlated to FEV which was not the case for lobectomy (114). Also, the positive cardiologic history is not a risk factor for increased postoperative morbidity and mortality for the elderly, on the assumption that lung resections will be limited to lobar, segmental or wedge resections (104,106,115,116). However, surgery for both middle and lower lobectomy (bilobectomy) was associated with significant cardio-respiratory postoperative complications compared to lower lobectomy (117).…”
Section: Discussionmentioning
confidence: 99%
“…Although the possibility for in-hospital death was estimated to be three times higher for the right-sided pneumonectomy compared to lobectomy or limited lung resection, the risk of death following pneumonectomy or extended resection was not correlated to FEV which was not the case for lobectomy (114). Also, the positive cardiologic history is not a risk factor for increased postoperative morbidity and mortality for the elderly, on the assumption that lung resections will be limited to lobar, segmental or wedge resections (104,106,115,116). However, surgery for both middle and lower lobectomy (bilobectomy) was associated with significant cardio-respiratory postoperative complications compared to lower lobectomy (117).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11] On the other hand the negative impact of COPD after pulmonary resec- The British Thoracic Society, in its guidelines on the selection of patients for lung cancer surgery, recommends that all patients should have equal access to lung cancer services regardless of age. 35 In a large retrospective study with 1073 patients, Takamochi et al reported that the rate of morbidity and mortality after pulmonary resection in elderly patients were similar to those observed in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…5 It is generally accepted that elderly patients with non-small cell lung cancer (NSCLC) should not be excluded from curative resection only due to their chronological age as the operative results in this group are similar to that of younger patients. [6][7][8][9][10][11] The negative impact of COPD after pulmonary resections for NSCLC has been discussed in several studies, but the following question still remains to be answered: How fit are elderly patients with COPD for lobar lung resection?…”
mentioning
confidence: 99%